Enterocolitis due to immune checkpoint inhibitors: a systematic review. Issue 11 (21st August 2018) - Soularue, Emilie; Lepage, Patricia; Colombel, Jean Frederic; Coutzac, Clelia; Faleck, David; Marthey, Lysiane; Collins, Michael; Chaput, Nathalie; Robert, Caroline; Carbonnel, Franck
Abstract : Immune checkpoint inhibitors targeting cytotoxic T-lymphocyte-associated protein-4 (CTLA-4) and programmed death-1 (PD-1)/ligand are increasingly used to treat several types of cancer. These drugs enhance antitumour T-cell activity and therefore induce immune-related adverse effects (irAE), of which gastrointestinal (GI) irAE are among the most frequent and severe. This systematic literature review summarises the clinical manifestations, management and pathophysiology of GI irAE due to immune checkpoint inhibitors. GI irAE induced by anti-CTLA-4 are frequent, potentially severe and resemble IBD, whereas those induced by PD-1 blockade seem to be less frequent and clinically more diverse. Baseline symbiotic gut microbiota is associated with an enhanced antitumour response to immune checkpoint inhibitors and an increased susceptibility to developing enterocolitis, in patients treated with anti-CTLA-4. These findings open new perspectives for possible manipulation of the gut microbiota in order to better identify responders to immune checkpoint inhibitors and to increase their efficacy and safety.